The importance of early recordings for the interpretation of late nineteenth-century French flute - Benatti, Antonella (Language and Public Sphere, 2024)
The characteristics of early recordings will be analyzed as evidence of the musical reality in which they were recorded. They will be then compared with the score and the Flute treatises of the time to understand any inconsistencies and limits.